Effect of time and dental substrate on the bond strength of a universal adhesive system: in vitro study - Poliana Maria de Faveri CARDOSO; Rafael da Silva VANOLLI; Fernanda Rafaela RIBEIRO; Marcio José MENDONÇA; Veridiana CAMILOTTI (Universidade Estadual Paulista, 2023)
Abstract Introduction Dentin adhesives provide union between the dental substrate and composite resin, but this union can be influenced by the cleaning agent. Objective Evaluate the use of ozonated water as a cavity cleaning solution. Material and method 40 bovine dental crowns were selected, divided into four groups: AD (dentin cleaning with distilled water) and AO (dentin cleaning with ozonized distilled water). Each group was divided into two storage periods (24h and 30 days) kept at 37 °C. The selected universal system adhesive was employed according to the manufacturer's instructions and light cured for 20 seconds. At that time, three cylinders were made (Tygon matrix with an internal diameter of 2 mm and a height of 2 mm) of composite resin in the crowns in the cervical, médium, and incisal regions and light cured for 30 seconds. After storage, the bonding strength was tested by micro-shear, and fracture type analysis was performed. The data were submitted to statistical analysis using the Shapiro-Wilk test with a significance level of 95%, ANOVA, and Turkey. Result There was a statistically significant difference between the bond strength values, only in the intergroup analysis for the time of 24 hours, between the middle third of the groups (LDAO24 = 2.70 (± 2.39); LDAO30 = 3.82 (± 2.31)). The predominant fracture type for both groups was an adhesive fracture, except in the medium and incisal thirds of the AD, which was a cohesive dentin fracture. Conclusion The utilization of ozone did not change the bond strength adhesive.